SUBSTITUIÇÃO DA SILAGEM DE CANA-DE-AÇÚCAR PELA SILAGEM DOS RESTOS CULTURAIS DO ABACAXIZEIRO NA ALIMENTAÇÃO DE RUMINANTES - SANTOS, Sandro de Castro (2008)
The objective of this trial was to study the substitution of sugar cane silage + 0,5% urea (SCS) by the pineapple stalk silage (PSS) on the feed ruminants. The trial was done in Goiânia-GO and lasted 95 days. Five non castrated male lambs from Santa Inês breed were utilized, with an average age of eight months and live weight of 30,2kg ± 4,8kg. The experimental design was a 5x5 Latin Square, the diets were isoproteic (13,5% CP) and isoenergetic (63% TDN) and the forage:concentrate ratio was 60:40. The parameters evaluated were the dry matter intake (DMI) and relative voluntary intake (RVI), apparent digestibility of nutrients, nutritive value index, physically effective fiber, rumen pH and rumen kinetics. The treatments were the following: 100% PSS:0% SCS (100P); 75% PSS:25% SCS (75P); 50% PSS:50% SCS (50P); 25% PSS:75% SCS (25P) and 0% PSS:100% SCS (0P). There were no differences (P>0,05) among treatments for the DMI (597,27 g/day) and RVI (58,41 g of MSU/day). The dry matter digestibility (DMD) and neutral detergent fiber digestibility (NDFD) did not differ (P>0,05) among diets. The crude protein digestibility (CPD) increased when SCS was linearly added, whose values were 68,09%; ,57%; 70,68%; 73,06% and 78,05%, respectively for the treatments 100P, 75P, 50P, 25P and 0P, which can be explained by the addition of 0,5% urea when the sugar cane was ensiled and characterizing the presence of non protein nitrogen (highly soluble in the rumen). It was not verified differences for the nutritive value index (NVI) among treatments, where the mean was 37,74%. Probably due to the DMI and DMD did not present differences (P>0,05) among treatments. Regarding the physically effective fiber (peNDF), there was not effect among treatments and the mean value was 25,92%. There was reduction in the ruminal digesta dry matter disappearance (%/h) with increasing addition of SCS. The values for this parameter were 8,08%/h; 8,31%/h; 5,85%/h; 6,49%/h and 7,03%/h respectively for the treatments 100P, 75P, 50P, 25P and 0P. Since there was no effect in the DMI among treatments and the ruminal digesta dry matter disappearance in the treatments having PSS was higher, it can be concluded that the dry matter digestion rate of the PSS was also higher. The rumen pH increased linearly with addition of SCS, where the values for the treatments 100P, 75P, 50P, 25P and 0P were respectively 6,16; 6,16; 6,33; 6,42 and 6,63. Based on the nutritive value it can be concluded that the sugar cane silage + 0,5% urea can be substituted by the pineapple stalk silage